Representasi Dualitas Peran Perempuan dalam Film Siti Sutradara Eddie Cahyono: Representation of the Duality of Women's Roles in the Film Siti Director Eddie Cahyono - Rahmin Meilani Putri; Nunung Afriani (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
The focus of this study is to describe the role of Siti as a wife and mother who has to deal with multiple layers of economic, social, and psychological pressures as a result of having to take care of the household while also being the main breadwinner for her family. This study aims to discuss the representation of dual roles experienced by female characters in Eddie Cahyono's film Siti. This study uses a qualitative descriptive approach with narrative analysis methods to reveal the representation of economic burdens, domestic burdens, as well as identity crises and female independence experienced by the main character. The results of the study show that the film Siti strongly depicts the condition of women trapped in dual roles. The character Siti must struggle with caring for her paralyzed husband, raising her children, and working at night as a karaoke hostess to meet her family's economic needs. The film also portrays Siti's identity crisis, her emotional alienation, and her difficulty in gaining recognition for her struggles. Thus, the film Siti serves as a vivid portrayal of the reality of women living within a patriarchal system and facing structural pressures that hinder their autonomy and well-being.